[Key words] nontargeted metabolomics , altitude-related hypertension , metabolic pathways , - CUI Haifeng; DUAN Daxin; ZHANG Xin (陆军军医大学学报, 2024)
Objective To explore the application value of functional movement screening (FMS) and targeted physical fitness training in military training for armored troops in cold area. Methods A total of 160 male new recruits were selected from an armored synthetic brigade by random number table method, and then divided into the experimental group and the control group (n=80). The common subjects in the military training program were given to the control group. Besides the common subjects, the experimental group were also given targeted physical fitness training, including core strength training and targeted movement correction training. Before and in 6 months after training, FMS test was carried out for the 2 groups. The occurrence of training injuries were observed and recorded in 2 groups during the 6 months of new training. Results Before the new training, there was no statistical difference in the FMS score between the experimental group and the control group (15.64±2.95 vs 15.67±3.42, P>0.05). After 6 months of training, the FMS score of the experimental group was 18.33±2.67, which was significantly higher than that of the control group (16.75±3.31, P < 0.05). The overall incidence of training injury was 12.50% in the experimental group, which was significantly lower than that in the control group, but no significant difference. In both groups, the incidence of training injury was significantly higher in those with FMS score < 14 than those with the score ≥14 from the same group (P < 0.05). The incidence in the experimental group with FMS score < 14 was 23.53% (4/17), significantly lower than that in the control group with FMS score < 14 [64.29% (9/14), P < 0.05]. Conclusion Application of FMS is conducive to understanding and judging the fundamental movements in officers and soldiers, and targeted physical fitness correction training can enhance their own physical quality and reduce the occurrence of training injuries.